S120 Reference values for the incremental shuttle walking test in a healthy population. (2nd December 2011) - Harrison, S L; Greening, N J; Houchen, L; Williams, J E A; Morgan, M; Steiner, M; Singh, S J
Abstract : Introduction: The assessment of functional exercise capacity is important in the evaluation of patients with chronic conditions and field walking tests are often used to assess functional exercise capacity. The ISWT is one field exercise test which is often employed in the assessment of pulmonary and cardiac rehabilitation (PR, CR) patients and also to prescribe a walking speed. In PR and CR programmes the ISWT is employed to calculate walking speed set at a desired training threshold. The aim of the study was to establish reference values for the ISWT and an equation for its prediction in a healthy population. This will allow comparison between patients from PR and CR programmes and healthy age-matched controls. Methods: Subjects were aged between 40 and 90 years, had normal spirometry defined as FEV1 % pred >80% and/or a FEV1 /FVC >70% and had no known co-morbidities affecting mobility. The best distance from two ISWT was recorded along with body mass index (BMI) and leg length. Quadriceps maximal voluntary contraction (QMVC: Kg) was measured using a strain gauge (Kern). Physical activity was assessed using the DUKE physical activity questionnaire and an activity monitor (SenseWear PRO 2 Armband). The number of steps and energy expenditure achieved over 2 days was recorded. Subjects also completed the Hospital Anxiety and Depression Scale. Results: 114 patients completed the study [mean (SD) age 60.48 (10.99) years, FEV1 108.82% (15.13) predicted, 37 male]. Mean ISWT distance was 690 m (152.68). There were no significant differences in walking distance between males and females (p>0.05). ISWT distance showed significant correlations with age, BMI, FEV1, QMVC, DUKE physical activity score and height (p<0.01). Stepwise multiple regression analysis showed that age, BMI, FEV1, QMVC and DUKE physical activity score were independent contributors to the ISWT distance achieved by healthy subjects, explaining 50.4% of the variance. (Abstract S120 figure 1 ). Conclusions: Variance in the ISWT can be measured using a composite score, comprising of: age, BMI, FEV1, QMVC and DUKE physical activity score. These findings would allow clinicians to express results of the ISWT as a percentage of the predicted values making results more meaningful for patients with chronic conditions.